2013
DOI: 10.1111/bjh.12594
|View full text |Cite
|
Sign up to set email alerts
|

Moderate endurance exercise in patients with sickle cell anaemia: effects on oxidative stress and endothelial activation

Abstract: SummaryVery few studies have investigated the effects of exercise on the biological parameters involved in vaso-occlusive events in sickle cell anaemia (SCA). The aim of this study was to test how a mild-moderate endurance exercise modulates oxidative stress, nitric oxide bioavailability and endothelial activation in SCA patients and healthy individuals. Eleven patients with SCA and 15 healthy subjects completed a 20-min duration submaximal cycling exercise at %45 Watts. Plasma markers of oxidative stress, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 44 publications
1
27
0
4
Order By: Relevance
“…Studies suggest that even moderate exercise can induce significant hypoxia in children with SCD, 86 impaired heart rate recovery, 87 abnormal increases in pulmonary artery pressure 88 and increased oxidative stress. 89 The clinical significance of these effects is unclear and studies in sickle mice suggested decreased oxidative stress with exercise. 90 Particular issues arise with some sports, such as swimming and skiing.…”
Section: Physical Activity and Sickle Cell Diseasementioning
confidence: 99%
“…Studies suggest that even moderate exercise can induce significant hypoxia in children with SCD, 86 impaired heart rate recovery, 87 abnormal increases in pulmonary artery pressure 88 and increased oxidative stress. 89 The clinical significance of these effects is unclear and studies in sickle mice suggested decreased oxidative stress with exercise. 90 Particular issues arise with some sports, such as swimming and skiing.…”
Section: Physical Activity and Sickle Cell Diseasementioning
confidence: 99%
“…Similar exercise programs could be a relevant option to prevent pulmonary complications in SCD patients because it has been observed in SCD subjects that moderate acute exercise does not alter their hemorheologic, oxidative stress, or hematologic parameters. 9,10 From these results, further studies performed on more severe SCD mice models and in SCD patients will have to confirm the efficiency and/or the benefits of PA in SCD, and to describe the underlying mechanisms of the therapeutic effect of exercise training in SCD.…”
mentioning
confidence: 99%
“…Two mechanistic models have been proposed regarding how such a germline predisposition may result in MPNs with clonal hematopoiesis. 9,10 First, the germline mutation could increase the mutation rate in JAK2 and CALR genes (hypermutability hypothesis), or second, it could synergize with JAK2-V617F or CALR in MPN disease initiation (fertile ground hypothesis). Because the G.T transversion in JAK2-V617F and the 52-base deletion in CALR are mechanistically very different, it seems unlikely that they could be promoted by the same germline mutation through a hypermutability mechanism.…”
mentioning
confidence: 99%
“…15 Evidence has shown that exercise and physical exertion can trigger the symptoms of the disease due to metabolic changes such as hypoxia, lactic acidosis, and dehydration. 16,17 In this case, the patient presented for the first time with renal disease. Around one half of SCD patients develop 18 Renal papillary infarction can result in painless hematuria that is gross in proportion, frequently reported among SCD patients and individuals with sickle cell trait.…”
Section: Discussionmentioning
confidence: 84%